PELATIHAN PENGGUNAAN ADMIN WEBSITE RUMAH DIGITAL GOMBENGSARI - Sony Panca Budiarto (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
Gombengsari digital home website is a technology-based tourism system that is integrated with MSMEs, lodging and travel agencies. This system is the result of the collaboration of the matching fund activities of a team of lecturers and students at STIKOM PGRI Banyuwangi with Pokdarwis Gombengsari as the coordinator of tourism, MSMEs, lodging and travel agencies in Gombengsari. The existence of this system is intended to provide solutions to the problems of Pokdarwis Gombengsari which have difficulty in introducing tourism potential, MSMEs, lodging and travel agencies in Gombengsari to local and international tourists. After the system was completed, another problem arose, namely that human resource knowledge related to the use of technology and digital information was still lacking. The gombengsari digital home website that has been created has never been updated. To overcome this, we as system developers will carry out community service activities, especially to the Gombengsari pokdarwis regarding how to use and operate the Gombengsari digital home website admin. The technical implementation of the service is devoted to conducting socialization, training and practicum to prospective gombengsari digital home web admins. In the implementation of training and practice, prospective gombengsari digital home web admins are provided with a manual for using the gombengsari digital home website. The results obtained during the Gombengsari digital home web admin training service activities are that the Gombengsari Pokdarwis already has a special operator that handles and manages the Gombengsari digital home website.